Sociodemographic and Cultural Determinants of Hypertension-Controlling Beliefs Among Older Adults: A Cross-Sectional Study Based on the Health Belief Model - Susilawati, Endang Fauziyah; Hidayat, Syaifurrahman; Amin, Edy Suryadi; Hakim, Arif Rahman; Nindawi, Nindawi (Journal of Applied Nursing and Health, 2026)
Background: Hypertension control among older adults in Indonesia is hindered by low adherence and strong cultural beliefs. However, there is insufficient evidence on how sociodemographic and cultural determinants interact with health belief constructs to influence hypertension-control beliefs in older populations. This study examines sociodemographic and cultural determinants of hypertension-controlling beliefs using the Health Belief Model (HBM). Methods: A cross-sectional study was conducted among 232 older adults (≥60 years) in coastal Madura, Indonesia. Data were collected via structured interviews using the HBM Questionnaire (HBMQ) and cultural belief items. Descriptive, bivariate, and multivariate analyses were performed. Results: Higher education, retirement, and perceiving hypertension as a lifestyle consequence were significantly associated with stronger beliefs (p < 0.05). Although 76.3% trusted doctors, 40.9% still visited traditional healers. Belief in lifestyle etiology was the strongest predictor (β = 0.20, p = 0.002). Conclusion: Cultural and educational factors significantly shape hypertension beliefs. Interventions should integrate biomedical education with cultural sensitivity to improve self-management in older populations.